Characteristics of patients who are not resuscitated in out of hospital cardiac arrests and opportunities to improve community response to cardiac arrest. (December 2016) - Rajagopal, S.; Kaye, C.R.; Lall, R.; Deakin, C.D.; Gates, S.; Pocock, H.; Quinn, T.; Rees, N.; Smyth, M.; Perkins, G.D.
Abstract: Aim: This study explores why resuscitation is withheld when emergency medical staff arrive at the scene of a cardiac arrest and identifies modifiable factors associated with this decision. Methods: This is a secondary analysis of unselected patients who sustained an out of hospital cardiac arrest attended by ambulance vehicles participating in a randomized controlled trial of a mechanical chest compression device (PARAMEDIC trial). Patients were categorized as 'non-resuscitation' patients if there was a do-not-attempt-cardiopulmonary-resuscitation (DNACPR) order, signs unequivocally associated with death or resuscitation was deemed futile (15 min had elapsed since collapse with no bystander-CPR and asystole recorded on EMS arrival). Results: Emergency Medical Services attended 11, 451 cardiac arrests. Resuscitation was attempted or continued by Emergency Medical Service staff in 4805 (42%) of cases. Resuscitation was withheld in 6646 cases (58%). 711 (6.2%) had a do not attempt resuscitation decision, 4439 (38.8%) had signs unequivocally associated with death and in 1496 cases (13.1%) CPR was considered futile. Those where resuscitation was withheld due to futility were characterised by low bystander CPR rates (7.2%) and by being female. Conclusions: Resuscitation was withheld by ambulance staff in over one in ten (13.1%) victims of out of hospital cardiac arrest on the basis of futility. These cases were associated with a very low rate of bystander CPR. Future studies should explore strengthening the 'Chain of Survival' to increase the community bystander CPR response and evaluate the effect on the numbers of survivors from out of hospital cardiac arrest.